Rekonstruksi Paradigma Transfer of Sentenced Persons: Antara Kepentingan Narapidana dan Kepentingan Negara, serta Implikasinya pada Tata Kelola Transfer of Sentenced Person - Arsil, Fitra (Jurnal Konstitusi & Demokrasi, 2025)
This article analyzes the paradigm shift in the Transfer of Sentenced Persons (TSP) from a regime oriented towards the rehabilitation and social reintegration of prisoners to a new configuration increasingly driven by state interests, such as national security, prison population management, immigration policy, budget efficiency, diplomatic calculations, and human rights image. Based on a legal-normative approach combined with institutional analysis and a comparison of practices in various jurisdictions, this paper shows how the principle of consensualism, initially interpreted as "trilateral consent" (the sentencing state, the receiving state, and the prisoner), has fragmented into three models: compulsory, voluntary, and hybrid, with direct implications for the autonomy of prisoners in the decision-making process. This article also shows how the classic prohibition on transferring prisoners sentenced to death through the TSP scheme is reconstructed through various sentence-conversion formulas and policy engineering. At the governance level, TSP is shifting from a predominantly judicial mechanism to a series of administrative and cross-sectoral coordination decisions, with the executive and inter-ministerial networks playing a central role.